Release film and film laminate

The film laminated body with a hardened silicone resin release layer and controlled particle content addresses the challenge of stable peeling and adhesion, ensuring ultra-light separation and low migration, suitable for extreme temperature environments.

JP7625909B2Active Publication Date: 2025-02-04MITSUBISHI CHEM CORP
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2021039728
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-11
Publication Date
2025-02-04
Estimated Expiration
2041-03-11

AI Technical Summary

Technical Problem

Existing films with adhesive layers face challenges in achieving stable, ultra-light peeling characteristics while maintaining strong adhesion and preventing blocking, especially in extreme temperature environments, due to issues with particle stability and migration in the release layer.

Method used

A film laminated body with a substrate film and a release layer containing a hardened silicone resin, having a specific thickness and elasticity, and optionally a polyester layer with controlled particle content, ensuring a maximum cross-sectional height and low migration, which enhances peeling performance and adhesion.

Benefits of technology

The proposed film laminated body achieves stable, ultra-light peeling with strong adhesion and low migration, even in extreme temperatures, while preventing blocking, making it suitable for applications requiring durable and reliable separation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007625909000001
    Figure 0007625909000001
  • Figure 0007625909000002
    Figure 0007625909000002
  • Figure 0007625909000003
    Figure 0007625909000003
Patent Text Reader

Abstract

To provide a new release film which is small in migration in addition to light peeling force, is difficult to be blocked, and has good adhesion to a base material.SOLUTION: A release film is provided, comprising has a base material film and a release layer provided on one surface side of the base material film, wherein the release layer includes a curable silicone resin, has a thickness of 0.2-1.5 μm and an elastic modulus at 25°C of 500 MPa or less, and does not substantially contain particles, and a maximum cross-sectional height (Rt) on a film surface opposite to a surface where the release layer is provided is larger than the thickness (μm) of the release layer and 2.0 μm or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a release film and a film laminate comprising a release film. [Background technology]

[0002] Polyethylene terephthalate (PET) film, a representative polyester film, especially biaxially oriented PET film, is used in a variety of fields, including industrial materials, optical materials, electronic component materials, and battery packaging materials, due to its excellent transparency, mechanical strength, heat resistance, and flexibility. 2. Description of the Related Art Release films having a polyester film substrate and a release layer formed by curing a curable silicone-based release agent containing a silicone resin as a main component are used in many fields.

[0003] In recent years, in applications where a pressure-sensitive adhesive layer is used, durability may be required more than ever before. For example, when a pressure-sensitive adhesive layer is used for bonding components of a touch panel mounted inside an automobile, the components must be firmly bonded together even when exposed to a high temperature atmosphere in summer or a low temperature environment in winter, since the application is outdoors. Therefore, with the improvement in durability of the pressure-sensitive adhesive layer itself, the adhesive strength of the pressure-sensitive adhesive layer itself has tended to be stronger than ever before. Therefore, the release film of a light release type that has been used widely in the past may be difficult to peel off from the pressure-sensitive adhesive layer, and there is a demand for even lighter release (i.e., ultra-light release).

[0004] When an attempt is made to increase the thickness of the release layer to achieve an ultra-light release of the release film, depending on the type of release agent used, migration components from the release layer may migrate to the surface of the adhesive layer, making it difficult to obtain the desired adhesive strength. On the other hand, when a release agent with low migration properties is used to suppress migration from the release layer, the transfer of migrating components to the surface of the adhesive layer is reduced, but on the other hand, if the release layer is applied thickly, the slipperiness of the release layer surface is poor, making it difficult to wind the film into a roll, or problems such as blocking of films may occur. In order to solve these problems, various proposals have been made to include fine particles in the release layer. (See, for example, Patent Documents 1 and 2.) [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2004-255704 A [Patent Document 2] JP 2017-61081 A Summary of the Invention [Problem to be solved by the invention]

[0006] However, while the inclusion of fine particles in the release layer prevents blocking, it is difficult to maintain the fine particles stably on the surface of the release layer, the release layer itself becomes brittle, and the release characteristics of the release layer are easily affected by particle fall-off, etc., so it may be difficult to obtain a release film with stable release force. On the other hand, as the release properties become lighter, the adhesion between the release layer and the base film tends to decrease, and it is very difficult to achieve both an extremely light release property for the adhesive layer and blocking resistance at a high level.

[0007] Therefore, an object of the present invention is to provide a release film that not only has a light peeling force but also has low migration and blocking resistance, and yet has good adhesion to a substrate, and a film laminate that includes this release film. [Means for solving the problem]

[0008] In view of the above circumstances, the present inventors have conducted intensive research and found that the above problems can be easily solved by using a release film having a specific composition, and have completed the present invention. That is, the present invention provides the following items [1] to

[16] . [1] A substrate film and a release layer provided on one side of the substrate film, the release layer contains a curable silicone resin, has a thickness of 0.2 to 1.5 μm, has an elastic modulus of 500 MPa or less at 25° C., and is substantially free of particles; A release film, wherein the maximum cross-sectional height (Rt) of the film surface opposite to the surface on which the release layer is provided is greater than the thickness (μm) of the release layer and is 2.0 μm or less. [2] The release film according to the above [1], wherein the surface of the base film opposite to the surface on which the release layer is provided is provided with a polyester layer containing 0.4 to 1.0 mass % of particles having an average particle size of 1 to 6 μm. [3] The release film according to any one of the above [1] or [2], further comprising a cured resin layer between the release layer and the base film. [4] The release film according to the above [3], wherein the cured resin layer is an antistatic layer. [5] The release film according to the above [3] or [4], wherein the cured resin layer is formed by curing a cured resin layer composition containing the following compounds (A) to (C): (A) A polymer in which a compound made of thiophene or a thiophene derivative is doped with another anionic compound, or a self-doped polymer having an anionic group in a compound made of thiophene or a thiophene derivative. (B) Polyhydroxy Compounds (C) One or more compounds selected from the group consisting of polyurethane resins, polyester resins, and acrylic resins. [6] The release film according to any one of the above [1] to [5], wherein the base film is a polyester film. [7] The release film according to [6] above, wherein the polyester film has a three-layer structure. [8] The release film according to any one of the above [1] to [7], wherein an acrylic adhesive tape ("No. 7475" manufactured by Tesa) is attached to the surface of the release film on which the release layer is to be formed, the tape is cut to a size of 50 mm x 300 mm, and the tape is left for 1 hour at room temperature. After that, the peel strength when peeled off at 180° under conditions of a tensile speed of 0.3 m / min is 10 g / inch or less. [9] The release film according to any one of the above [1] to [8], which is a roll of the release film wound in a roll shape.

[10] The release film according to any one of the above [1] to [9], which is for mounting on a vehicle.

[11] A film laminate comprising the release film according to any one of [1] to

[10] above, an adhesive layer laminated on the release layer side of the release film, and another release film bonded to the adhesive layer.

[12] The film laminate according to the above

[11] , wherein the adhesive layer is formed from an acrylic adhesive composition.

[13] The film laminate according to the above

[11] or

[12] , wherein the modulus of elasticity of the adhesive layer at 25°C is 20 MPa or more.

[14] The film laminate according to any one of the above

[11] to

[13] , which is for mounting on a vehicle.

[15] A method for using the film laminate according to any one of

[11] to

[14] above, comprising peeling off the release film according to any one of [1] to

[10] above, and then bonding the exposed adhesive layer surface to an optical component.

[16] A method for using the film laminate according to the above

[15] , wherein the optical component is a polarizing plate or a touch sensor. Effect of the Invention

[0009] The release film and film laminate proposed by the present invention are not only light in peel strength, but also have low migration and blocking resistance, and have good adhesion to the substrate. Therefore, the release film proposed by the present invention is particularly suitable for protecting adhesive layers with strong adhesive strength. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Next, an example of an embodiment of the present invention will be described. However, the present invention is not limited to the embodiment described below.

[0011] <<<Release film>>> A release film according to an embodiment of the present invention (hereinafter, sometimes referred to as "this release film") is a release film including a base film and a release layer (hereinafter, sometimes referred to as "this release layer") provided on one side of the base film. The release film is wound up into a roll of release film (release film roll) and may be stored in the form of a release film roll. The release film may have a release layer on at least one side of the base film. In the release film, the surface opposite to the surface on which the release layer is provided may be referred to as the "opposite release surface" in the following description. The release film may have release layers on both sides of the base film. The release film may also have another layer between the base film and the release layer, or may have another layer other than the release layer on the surface of the base film on which the release layer is not provided. Therefore, the "opposite release surface" may be the surface of the base film itself, but may also be composed of a release layer or a layer other than a release layer.

[0012] In this release film, the release layer contains a curable silicone resin, has a thickness of 0.2 to 1.5 μm, has an elastic modulus of 500 MPa or less at 25° C., and is substantially free of particles. In addition, the maximum cross-sectional height (Rt: μm) of the surface of the release film opposite to the surface on which the release layer is provided (non-release surface) is greater than the thickness (μm) of the release layer and is 2.0 μm or less. When the release film having the above-mentioned configuration is rolled, the non-release surface is superimposed on the surface of the release layer, and at that time, the non-release surface is prevented from adhering to the release layer, thereby suppressing the occurrence of blocking. In addition, the release layer has a small peeling force and realizes an ultra-light peelability, while also having good adhesion to the substrate, and furthermore, it is possible to suppress the transfer of the release agent component to the adhesive tape, etc.

[0013] <Base film> The base film in the release film is not particularly limited in material as long as it has a film shape. For example, it may be made of paper, resin, metal, etc. Among these, it is preferable to use a resin from the viewpoint of mechanical strength and flexibility.

[0014] Examples of the resin substrate film include films formed from polymers such as polyethylene, polypropylene, polyester, polystyrene, polycarbonate, polyethersulfone, polyamide, polyimide, etc. Furthermore, as long as they can be formed into a film, they may be mixtures of these materials (polymer blends) or composites of their constituent units (copolymers).

[0015] Among the above-mentioned films, polyester films are particularly preferred because they have excellent physical properties such as heat resistance, flatness, optical properties, and strength. The polyester film may be a single layer film or a multilayer film (laminate film) having two or more layers with different properties. The polyester film may be a non-stretched film (sheet) or a stretched film. Of these, a uniaxially or biaxially stretched film is preferred. Of these, a biaxially stretched film is more preferred from the viewpoints of balance of mechanical properties and flatness.

[0016] The polyester that is the main component resin of the polyester film may be either a homopolyester or a copolymer polyester. The term "main component resin" refers to the resin that has the largest mass proportion among the resins constituting the polyester film, and is expected to account for 50 mass% or more, 75 mass% or more, 90 mass% or more, or 100 mass% of the resins constituting the polyester film.

[0017] The homopolyester is preferably one obtained by polycondensation of an aromatic dicarboxylic acid and an aliphatic glycol, such as terephthalic acid or 2,6-naphthalenedicarboxylic acid, or ethylene glycol, diethylene glycol, 1,4-butanediol, or 1,4-cyclohexanedimethanol. Representative examples of homopolyester include polyethylene terephthalate (PET) and polybutylene terephthalate (PBT).

[0018] Examples of the copolymer polyester include those obtained by polycondensing a dicarboxylic acid component and a glycol component. Examples of the dicarboxylic acid component of the copolymer polyester include one or more of isophthalic acid, phthalic acid, terephthalic acid, 2,6-naphthalenedicarboxylic acid, adipic acid, sebacic acid, etc., and examples of the glycol component include one or more of ethylene glycol, diethylene glycol, propylene glycol, 1,4-butanediol, 1,4-cyclohexanedimethanol, neopentyl glycol, etc. The copolymer polyester is preferably a copolymer containing 30 mol % or less of a third component based on the total of the dicarboxylic acid component and the glycol component.

[0019] Among the above, the polyester used in the base film of the release film is preferably polyethylene terephthalate, for example, in which 60 mol % or more, preferably 80 mol % or more is an ethylene terephthalate unit.

[0020] Particles can be blended into the base film of the release film for the main purpose of imparting easy slippage and preventing scratches in each process.When particles are blended, the type of particles to be blended is not particularly limited as long as it is a particle that can impart easy slippage, and specific examples include inorganic particles such as silica, calcium carbonate, magnesium carbonate, barium carbonate, calcium sulfate, calcium phosphate, magnesium phosphate, kaolin, aluminum oxide, and titanium oxide, and organic particles such as acrylic resins, styrene resins, urea resins, phenolic resins, epoxy resins, and benzoguanamine resins.Furthermore, precipitated particles obtained by precipitating and finely dispersing a part of a metal compound such as a catalyst during the polyester manufacturing process can also be used.

[0021] On the other hand, the shape of the particles to be used is not particularly limited, and any of spherical, blocky, rod-like, flat, etc. may be used. In addition, there is no particular limit to the hardness, specific gravity, color, etc. Two or more kinds of these particles may be used in combination as necessary.

[0022] The average particle size of the particles used is preferably 0.1 to 6 μm, more preferably 0.5 to 5 μm, and particularly preferably 1 to 4 μm. By using particles with an average particle size in the above range, an appropriate surface roughness can be imparted to the film, and good slipping properties and smoothness can be ensured. The average particle size of particles can be calculated by measuring the diameters of 10 or more particles using an optical microscope or a scanning electron microscope (SEM) and taking the average value. In this case, if the cross-sectional shape is other than a circle, such as an ellipse, the average value of the longest and shortest diameters can be measured as the diameter of each particle.

[0023] Furthermore, the particle content in the base film is preferably 5% by mass or less, more preferably in the range of 0.001 to 3% by mass, and even more preferably 0.01 to 1% by mass. When there are no particles or when there are only a few particles, the transparency of the film is high and a good film is obtained, but in order to prevent the lubricity from decreasing, it may be necessary to take measures such as adding particles to the coating layer to improve the lubricity. Moreover, the transparency of the film can be ensured by suppressing the particle content.

[0024] The polyester film may have a multi-layer structure of two or more layers, but a polyester film having a three-layer structure is preferred. In the case of a three-layer structure, as described below, even if particles are contained in the polyester layers (surface layers) on both surfaces, particles do not need to be contained in the intermediate layer. Therefore, the transparency of the polyester film can be improved while improving the slipperiness and blocking resistance. The polyester constituting each layer is as described above.

[0025] In addition, when the polyester film has a multi-layer structure of two or more layers, the average particle size of the particles used in the polyester layer on the side opposite to the side on which the release layer is provided (typically, the polyester layer on the side on which the release layer is not provided) is preferably 1 to 6 μm, more preferably 2 to 5 μm, and particularly preferably 3 to 5 μm. The particle content in the polyester layer is, for example, 0.03 to 1.0 mass%, preferably 0.3 mass% to 1.0 mass%, more preferably 0.4 to 1.0 mass%, and particularly preferably 0.4 to 0.8 mass%. By simultaneously satisfying the above average particle size and addition amount, the opposite release surface has a large maximum cross-sectional height (Rt) and has a moderate uneven shape, and the release film can achieve both blocking prevention and releasability. Even when the polyester film is composed of a single layer, the single polyester layer may contain particles from the viewpoints of anti-blocking resistance and releasability, and the average particle size and the amount of added particles may be within the ranges described above.

[0026] In a two-layer or more polyester film, the polyester layer (surface layer) on the side on which the release layer is provided may or may not contain particles, but it is preferable that it contains particles from the viewpoint of slipperiness, etc. The particle content (mass %) in the polyester layer (surface layer) on the side on which the release layer is provided is preferably lower than the particle content (mass %) in the polyester layer on the side opposite to the side on which the release layer is provided. Specifically, the particle content (mass %) in the polyester layer on the side on which the release layer is provided is preferably in the range of 0.001 to 0.8 mass %, more preferably 0.01 to 0.5 mass %, and even more preferably 0.02 to 0.2 mass %.

[0027] <Production method of polyester film> As an example of the method for producing a polyester film, a case where the polyester film is a biaxially stretched film will be described below, although the method is not limited to the method described here.

[0028] First, using a known method, raw materials, such as polyester chips, are fed into a melt extrusion device, heated to above the melting point of each polymer, and the molten polymer is extruded through a die and cooled and solidified on a rotating cooling drum to a temperature below the glass transition point of the polymer, thereby obtaining an unoriented sheet in a substantially amorphous state. Next, the unoriented sheet is stretched in one direction by a roll or tenter type stretching machine, at a stretching temperature of usually 25 to 120° C., preferably 35 to 100° C., and a stretching ratio of usually 2.5 to 7 times, preferably 2.8 to 6 times. Then, the film is stretched in a direction perpendicular to the first-stage stretching direction at a temperature of usually 50 to 140° C. and a stretch ratio of usually 3.0 to 7 times, preferably 3.5 to 6 times. Then, the polyester film is heat-set at a temperature of 130 to 270° C. under tension or under relaxation of 30% or less, to obtain the present polyester film as a biaxially oriented film. In the above-mentioned stretching, a method in which the stretching in one direction is carried out in two or more stages can also be adopted.

[0029] <<Main release layer>> The release layer is a layer formed by curing a release layer composition (referred to as the "release layer composition") containing a curable silicone resin (the "curable silicone resin") as a main component resin, and is disposed on at least one side of the above-mentioned base film. The release layer can also be said to be a release layer containing a cured product formed by curing the release layer composition.

[0030] <This release layer composition> The release layer composition may be any composition containing a curable silicone resin as a main component resin. The present release layer composition may contain components other than the curable silicone resin, and may contain, as necessary, for example, a catalyst, a reaction control agent, a crosslinking agent, a polymerization initiator, a diluent solvent, and other additives.

[0031] In addition, the above-mentioned "main component resin" means the resin that has the largest mass proportion among the resins that make up this release layer composition, and is expected to account for 50 mass% or more, or 75 mass% or more, or 90 mass% or more, or 100 mass% of the resins that make up this release layer composition.

[0032] When the present release layer composition contains a certain amount of vinyl groups relative to the total amount of siloxane components, the release layer is sufficiently cured, and the amount of alkenyl groups, i.e., vinyl groups, is not excessive, so that the peeling force after exposure to air can be prevented from becoming heavy. For these reasons, the present release layer composition preferably contains 0.4 to 1.0 mol% of vinyl groups relative to the total amount of siloxane components. Among these, it is more preferable that the present release layer composition contains 0.5 mol% or more of vinyl groups, particularly preferably 0.6 mol% or more, and particularly preferably 0.9 mol% or less of vinyl groups. When the release layer composition contains a certain amount of Si-H groups relative to the total amount of siloxane components, the release layer is sufficiently cured, and on the other hand, by preventing the amount of Si-H groups from becoming excessive, the Si-H groups remaining after curing are prevented from reacting with the adhesive layer, and the release film can be prevented from peeling off easily. For these reasons, the release layer composition preferably contains 0.8 to 2.2 mol% of Si-H groups relative to the total amount of siloxane components, more preferably 1.2 mol% or more, particularly preferably 1.4 mol% or more, more preferably 2.1 mol% or less, and particularly preferably 2.0 mol% or less of Si-H groups.

[0033] The total content of siloxane components in the release layer composition can be measured, for example, by 1H-NMR from the integral ratio of the dimethylsiloxane unit in the main chain to the other units. The vinyl group and Si-H group contents indicate the ratio to the total amount of functional groups bonded to the siloxane chain, and can be evaluated by measuring 1H-NMR. However, the method is not limited to this.

[0034] <Fully cured silicone resin> In the present invention, the term "curable silicone resin" refers to a silicone resin that has the property of being able to be cured. The curing method of the curable silicone resin is arbitrary. For example, it may be a resin that reacts with moisture in the air to cure through a condensation reaction, a resin that cures through an addition reaction caused by heating, or a resin that cures through addition polymerization or radical polymerization caused by light. Among these, thermosetting silicone resins that cure through an addition reaction caused by heating are preferred, since they do not produce by-products in the curing reaction and the physical properties of the cured film are stable. When the present curable silicone resin is a thermosetting type, it is characterized in that an alkenyl group such as a vinyl group (Vi group) or a hexenyl group is introduced into the side chain and / or the terminal of the main chain consisting of a siloxane bond in the structure.

[0035] The fully curable silicone resin may be any polymer having a main chain of siloxane bonds consisting of silicon and oxygen. Examples of the present curable silicone resin include those in which various substituents have been introduced into the side chains or terminals of the main chain consisting of siloxane bonds. In this case, the substituents can include, for example, any one of methyl groups, phenyl groups, polyethers, epoxy groups, amines, carboxyl groups, aralkyl groups, etc., or a combination of two or more of them.

[0036] An example of the present curable silicone resin is a silicone resin in which a Si-H group (also simply referred to as an "H group") and a vinyl group are introduced into a side chain or terminal of a linear main chain consisting of a siloxane bond.

[0037] The content of Si-H groups in the present curable silicone resin is preferably 0.8 to 2.2 mol % of Si-H groups relative to the total amount of siloxane components, more preferably 1.2 mol % or more, particularly preferably 1.4 mol % or more, more preferably 2.1 mol % or less, and particularly preferably 2.0 mol % or less. The vinyl group content in the present curable silicone resin is preferably 0.4 to 1.0 mol % of the total amount of siloxane components, more preferably 0.5 mol % or more, even more preferably 0.6 mol % or more, and still more preferably 0.9 mol % or less.

[0038] The present curable silicone resin may be a combination of two or more curable silicone resins. In this case, the content ratio of each of the above-mentioned functional groups is preferably within the above-mentioned ranges, that is, the content of vinyl groups and the amount of Si-H groups in the entire two or more curable silicone resins. When using two or more kinds of curable silicone resins, for example, a curable silicone resin (base) having an alkenyl group such as a vinyl group and a silicone resin (also called a silicone crosslinking agent) having a Si-H group can be used in combination. By using the base and the silicone crosslinking agent in combination, the base and the silicone crosslinking agent can be mixed and heated to cause an addition reaction, thereby appropriately curing the release layer composition. The vinyl group content in the curable silicone resin constituting the base resin is preferably 0.4 to 2.5 mol%, more preferably 0.5 mol% or more, even more preferably 0.6 mol% or more, more preferably 2.0 mol% or less, even more preferably 1.5 mol% or less.

[0039] The number average molecular weight (Mn) of the curable silicone resin is preferably 9,000 or more and 350,000 or less. When the number average molecular weight (Mn) of the present curable silicone resin is set to the above lower limit value or more, when an adhesive layer is laminated on the present release film, the amount of low molecular weight silicone resin that dissolves or migrates to the adhesive layer can be reduced, and the present release layer can be applied thickly to easily obtain a light peeling effect. On the other hand, when the number average molecular weight (Mn) of the present curable silicone resin is set to the above upper limit value or less, the viscosity increases and the flowability of the present release layer composition is prevented from decreasing. Therefore, when the present release layer composition is applied, streaky coating unevenness is prevented from occurring, and the present release layer surface is easily made smooth. From this viewpoint, the number average molecular weight (Mn) of the present curable silicone resin is preferably 9000 or more, more preferably 10000 or more, even more preferably 20000 or more, and even more preferably 30000 or more. On the other hand, it is preferably 350000 or less, more preferably 50000 or less, and even more preferably 40000 or less.

[0040] From the same viewpoint as for the number average molecular weight, the mass average molecular weight (Mw) of the present curable silicone resin is preferably 10,000 to 500,000, more preferably 20,000 or more, even more preferably 50,000 or more, and particularly preferably 80,000 or more, and is more preferably 250,000 or less, and even more preferably 100,000 or less.

[0041] The present curable silicone resin preferably has a ratio (Mw / Mn) of the mass average molecular weight (Mw) to the number average molecular weight (Mn) of 1.7 to 2.7, more preferably 1.9 or more, and even more preferably 2.5 or less. By satisfying this range, it is expected that the crosslinking reaction will proceed efficiently. The number average molecular weight (Mn) and the mass average molecular weight (Mw) are values ​​obtained by gel permeation chromatography (GPC) measurement using polystyrene as a standard. The specific measurement method is to measure the chromatogram using a GPC measurement device, and the number average molecular weight (Mn) and the weight average molecular weight (Mw) are obtained based on a calibration curve using standard polystyrene, as shown in Table 2. Specifically, 4 mg of the sample for measurement was dissolved in 4 mL of THF to prepare a measurement solution, and 100 μL of the measurement solution was injected into the GPC measurement device for measurement. Tetrahydrofuran (THF) was used as the eluent. For the analysis, Tosoh Corporation's "Ecosec8320" was used, Tosoh Corporation's "TSKgel guardcolumn HXL-L" was used as the guard column, and four Tosoh Corporation's "TSKgel GMHXL" were used in connection as the column. The analysis was performed under the conditions of an oven temperature of 40°C and a THF flow rate of 1.0 mL / min, and RI was used for detection.

[0042] The present curable silicone resin may be a combination of two or more curable silicone resins, in which case the average molecular weight of the two or more curable silicone resins is preferably within the above range. Note that the average here is a weighted average weighted by the mass of each resin. Furthermore, when a base resin and a silicone crosslinking agent are used as the curable silicone resin, it is preferable that the number average molecular weight, mass average molecular weight, and Mw / Mn of the base resin are within the above-mentioned ranges.

[0043] The present curable silicone resin preferably has a viscosity of 1 to 400 mcps at 25° C. when diluted with n-heptane solvent to adjust the concentration to 15% by mass. If the viscosity of the present curable silicone resin is 1 mcps or more, the appropriate viscosity of the coating liquid suppresses repelling and results in a good coat appearance, which is preferable. If the viscosity is 400 mcps or less, the fluidity of the present release layer composition can be maintained, the occurrence of streaky coating unevenness when the present release layer composition is applied can be suppressed, and the surface of the present release layer can be made smooth, which is preferable. From this viewpoint, the viscosity of the present curable silicone resin is more preferably 5 mcps or more, more preferably 10 mcps or more, and more preferably 300 mcps or less, more preferably 200 mcps or less. The viscosity was measured by diluting the curable silicone resin with n-heptane to 15% by mass, and measuring the viscosity of this solution at 25° C. using an E-type viscometer (Toki Sangyo Co., Ltd., “TVE-22L”).

[0044] The present curable silicone resin may be either a solventless curable silicone or a solvent curable silicone, or a combination of both. Here, "solventless curable silicone" refers to a silicone with a viscosity that allows it to be applied without diluting it with a solvent, and is a silicone resin that is made of short polysiloxane chains and has a relatively low molecular weight. On the other hand, "solvent-curable silicone" is a silicone resin that is so viscous that it cannot be applied unless it is diluted with a solvent, and is a silicone that has a relatively high molecular weight compared to solventless-curable silicone. In particular, it is preferable that the present curable silicone resin has a medium number average molecular weight (Mn) and a medium viscosity, as described above, and furthermore, it is preferable that the present curable silicone resin is a solvent-type curable silicone, from the viewpoints of providing good adhesion to the present substrate film, providing a good coating appearance without uneven coating, and facilitating adjustment of the film thickness of the present release layer.

[0045] The release layer, i.e., the release layer composition, does not substantially contain particles. By substantially not containing particles, the release layer can stabilize the release characteristics while reducing migration. Incidentally, "substantially not containing" means that the release layer (release layer composition) may contain particles as long as the amount is small enough not to impair the effects of the present invention, and may contain, for example, particles that are inevitably mixed in. The specific content of particles in the release layer is, for example, less than 0.05% by mass, preferably less than 0.01% by mass, more preferably less than 0.0001% by mass, based on the non-volatile components. The range of the content of particles in this release layer composition based on the non-volatile components is also the same as the content of the particles described above.

[0046] <Other ingredients> In addition to the present curable silicone resin, the present release layer composition may contain, as necessary, for example, a curing catalyst, a diluting solvent, a reaction control agent, a crosslinking agent other than the above-mentioned silicone crosslinking agent, a polymerization initiator, an adhesion enhancer, and other additives. For example, one example of the release layer composition can be a composition containing a curable silicone resin (main agent) having an alkenyl group such as a vinyl group, a silicone crosslinking agent having a hydrosilyl group (SiH group) at the side chain and / or end of the main chain consisting of a siloxane bond, a catalyst containing platinum (Pt) (platinum-based catalyst), and a solvent.

[0047] (catalyst) As described above, the release layer composition may optionally contain a curing catalyst, i.e., a catalyst for promoting the hydrosilylation addition reaction between the alkenyl groups bonded to the silicon atoms of the curable silicone resin and the hydrogen silane (SiH) groups of the silicone crosslinker. Examples of the curing catalyst include platinum-based catalysts such as platinum black, platinic chloride, chloroplatinic acid, reaction products of chloroplatinic acid and monohydric alcohols, complexes of chloroplatinic acid and olefins, platinum group metal catalysts such as platinum bisacetoacetate, palladium catalysts, and rhodium catalysts, but are not limited to these.

[0048] The content of the curing catalyst in the present release layer composition is preferably 0.5 to 500 ppm by mass, more preferably 5 ppm by mass or more, and even more preferably 10 ppm by mass or more, more preferably 300 ppm by mass or less, and even more preferably 200 ppm by mass or less, relative to the curable silicone resin.

[0049] (Dilution solvent) As described above, the release layer composition may contain a dilution solvent as necessary. Examples of the dilution solvent include aromatic hydrocarbons such as toluene, aliphatic hydrocarbons such as hexane, heptane, and isooctane, esters such as ethyl acetate and butyl acetate, ketones such as ethyl methyl ketone (MEK) and isobutyl methyl ketone, alcohols such as ethanol and 2-propanol, and ethers such as diisopropyl ether and dibutyl ether. These are preferably used alone or in combination, taking into consideration solubility, coatability, boiling point, and the like.

[0050] (Reaction control agent) As described above, the release layer composition may contain a reaction inhibitor as necessary. Examples of the reaction inhibitor include acetylene alcohol. The reaction inhibitor may be one type, or two or more types may be used in combination as necessary. The content of the reaction inhibitor is preferably 0.001 to 5.0 parts by mass, more preferably 0.01 parts by mass or more, even more preferably 0.05 parts by mass or more, more preferably 1.0 parts by mass or less, and even more preferably 0.5 parts by mass or less, per 100 parts by mass of the total amount of the release layer composition (based on non-volatile components).

[0051] <Thickness of this release layer> The thickness of the release layer must be in the range of 0.2 to 1.5 μm in order to achieve ultra-light release. If the thickness of the release layer is less than 0.2 μm, it is difficult to achieve ultra-light release even if the elastic modulus of the release layer is within a predetermined range, as described below. If the thickness is greater than 1.5 μm, the release agent component may increase in migration to the adhesive tape or blocking may not be sufficiently prevented. From the viewpoint of achieving ultra-light release, preventing blocking, and suppressing the increase in migration, the thickness of the release layer is preferably 0.4 to 1.3 μm, more preferably 0.5 to 1.0 μm.

[0052] <<Other layers>> The release film may have "another layer" between the base film and the release layer. The "other layer" may be, for example, a layer having various functions such as an antistatic layer, an oligomer sealing layer, etc. The layer provided between the present substrate film and the release layer may be a cured resin layer, and a cured resin layer that is an antistatic layer is preferable.

[0053] Specifically, in the release film of the present invention, from the viewpoint of preventing adhesion and inclusion of foreign matter from the outside, it is preferable to provide a cured resin layer obtained by curing a cured resin layer composition containing the following compounds (A) to (C) between the release layer and the base film. Furthermore, a cured resin layer may be provided on the surface of the base film on which no release layer is provided. The cured resin layer may be an antistatic layer or the like, and specifically may be a cured resin layer obtained by curing a cured resin layer composition containing the following compounds (A) to (C).

[0054] (A) A polymer (a) in which a compound consisting of thiophene or a thiophene derivative is doped with another anionic compound, or (b) a self-doped polymer having an anionic group in a compound consisting of thiophene or a thiophene derivative. Examples of compound (A) include those obtained by polymerizing a compound of the following formula (1) or (2) in the presence of a polyanion. Polymer (a) and polymer (b) may be used in combination.

[0055] [ka]

[0056] In the above formula (1), R 1 and R 2 each independently represents a hydrogen atom or an aliphatic hydrocarbon group, an alicyclic hydrocarbon group, an aromatic hydrocarbon group, or the like having 1 to 20 carbon atoms.

[0057] [ka]

[0058] In the above formula (2), n represents an integer of 1 to 4.

[0059] Examples of polyanions used in polymerization include poly(meth)acrylic acid, polymaleic acid, polystyrene sulfonic acid, polyvinyl sulfonic acid, etc. As a method for producing such a polymer, for example, a method such as that shown in JP-A-7-90060 can be adopted.

[0060] In the present invention, the compound of the above formula (2) in which n is 2 and polystyrene sulfonic acid is used as the polyanion is preferably used.

[0061] When these polyanions are acidic, they may be partially or completely neutralized. The base used for neutralization is preferably ammonia, organic amines, or alkali metal hydroxides.

[0062] The proportion of the compound (A) in the total non-volatile components in the cured resin layer composition is usually 5 to 80 mass%, preferably 5 to 50 mass%, more preferably 5 to 30 mass%. By making the proportion of the compound (A) equal to or less than the upper limit, the strength and transparency of the cured resin layer can be prevented from becoming insufficient. On the other hand, if the proportion of the compound (A) is equal to or more than the lower limit, the antistatic property can be prevented from becoming insufficient.

[0063] (B): Polyhydroxy compound Compound (B) is one or more polyhydroxy compounds, and is defined as a compound having two or more hydroxyl groups in its molecular structure. As the polyhydroxy compound, it is preferable to use sugars or sugar alcohols from the viewpoint of electrical conductivity. Compound (B) also includes sugar alcohol derivatives such as condensates of monosaccharides or disaccharides and polyhydroxy compounds. Specific examples of sugar alcohols include, for example, maltitol, isomaltulose reduction product (palatinit) obtained by reducing isomaltulose, lactitol, erythritol, sorbitol, xylitol, mannitol, ribitol, arabitol, iditol, talitol, galactitol, and the like, all of which are C4 or higher compounds. Sugar alcohols may be used alone or in combination of two or more. Among sugar alcohols, from the viewpoint of achieving both high electrical conductivity and high transparency, sugar alcohols obtained by reducing disaccharides or trisaccharides are preferred, and it is even more preferred that the molecular weight of the sugar alcohol is 200 or more and 600 or less and that the hydroxyl group equivalent weight is 40 or less. Among these, the sugar alcohols corresponding to disaccharides, such as maltitol, lactitol, and reduced products of isomaltulose, are particularly preferred. As the polyhydroxy compound, polyglycerin having an average degree of polymerization of 2 to 9, preferably 2 to 8, and alkylene oxide adducts to polyglycerin can be used. The alkylene oxide adducts to polyglycerin have a structure in which alkylene oxide is added and polymerized to the hydroxyl group of polyglycerin. The alkylene oxide is preferably ethylene oxide or propylene oxide.

[0064] The proportion of the compound (B) in the total non-volatile components in the cured resin layer composition is usually 5 to 80 mass%, preferably 5 to 50 mass%, more preferably 10 to 30 mass%. When the proportion of the compound (B) is equal to or less than the upper limit, the proportions of other components can be prevented from decreasing, and antistatic properties and coating appearance can be prevented from becoming insufficient. On the other hand, when the proportion of the compound (B) is equal to or more than the lower limit, precipitation of oligomers can be sufficiently suppressed, and a decrease in film-forming properties can be prevented, making it easier to obtain a uniform coating film.

[0065] (C): One or more compounds selected from the group consisting of polyurethane resins, polyester resins, and acrylic resins. When the cured resin layer composition contains one or more compounds selected from the group consisting of polyurethane resins, polyester resins, and acrylic resins, the film-forming properties, transparency, antistatic properties, etc. of the cured resin layer are improved. The component (C) serves as a binder in the cured resin layer.

[0066] (polyester resin) The polyester resin may be composed of, for example, the following polyvalent carboxylic acid and polyvalent hydroxy compound as main components. That is, as the polyvalent carboxylic acid, terephthalic acid, isophthalic acid, orthophthalic acid, phthalic acid, 4,4'-diphenyldicarboxylic acid, 2,5-naphthalenedicarboxylic acid, 1,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, 2,7-naphthalenedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, 2-potassium sulfoterephthalic acid, 5-sodium sulfoisophthalic acid, adipic acid, azelaic acid, sebacic acid, dodecanedicarboxylic acid, glutaric acid, succinic acid, trimellitic acid, trimesic acid, pyromellitic acid, trimellitic anhydride, phthalic anhydride, p-hydroxybenzoic acid, trimellitic acid monopotassium salt, and ester-forming derivatives thereof may be used. Examples of polyhydric hydroxy compounds that can be used include ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,3-propanediol, 1,4-butanediol, 1,6-hexanediol, 2-methyl-1,5-pentanediol, neopentyl glycol, 1,4-cyclohexanedimethanol, p-xylylene glycol, bisphenol A-ethylene glycol adduct, diethylene glycol, triethylene glycol, polyethylene glycol, polypropylene glycol, polytetramethylene glycol, polytetramethylene oxide glycol, dimethylolpropionic acid, glycerin, trimethylolpropane, sodium dimethylolethylsulfonate, and potassium dimethylolpropionate. The polyester resin is a polycondensation product of a polyvalent carboxylic acid and a polyvalent hydroxy compound. One or more polyvalent carboxylic acids and one or more polyvalent hydroxy compounds are appropriately selected from the above-mentioned compounds, and the polyester resin may be synthesized by a conventional polycondensation reaction. The polyester resin may be made into a water dispersion, and in this case, a hydrophilic functional group or the like may be appropriately introduced into the polyester resin.

[0067] (urethane resin) The urethane resin is a polymeric compound having a urethane bond in the molecule. Usually, the urethane resin is produced by the reaction of a polyol with an isocyanate. The polyol may be polycarbonate polyols, polyester polyols, polyether polyols, polyolefin polyols, or acrylic polyols, and these compounds may be used alone or in combination. The urethane resin may be a water dispersion, and in this case, for example, a hydrophilic functional group may be appropriately introduced into the polyol.

[0068] (Acrylic resin) The acrylic resin is a polymer made of polymerizable monomers including acrylic and methacrylic monomers. These may be homopolymers or copolymers, or copolymers with polymerizable monomers other than acrylic and methacrylic monomers. Also included are copolymers of these polymers with other polymers (such as polyesters and polyurethanes). For example, block copolymers and graft copolymers. That is, the acrylic resin may be an acrylic-modified polyester resin or an acrylic-modified polyurethane resin. Further, it also includes a polymer (or a mixture of polymers, in some cases) obtained by polymerizing a polymerizable monomer in a polyester solution or polyester dispersion. Similarly, it also includes a polymer (or a mixture of polymers, in some cases) obtained by polymerizing a polymerizable monomer in a polyurethane solution or polyurethane dispersion. Similarly, it also includes a polymer (or a mixture of polymers, in some cases) obtained by polymerizing a polymerizable monomer in another polymer solution or dispersion, and these are also referred to as acrylic-modified polyester resins and acrylic-modified polyurethane resins in this specification. The above-mentioned polyesters and polyurethanes used in the acrylic resins can be appropriately selected from those exemplified as the polyesters and polyurethanes as the component (C) above. The acrylic resin may contain a hydroxyl group or an amino group in order to further improve adhesion to the base film.

[0069] The polymerizable monomer is not particularly limited, but particularly representative compounds include various carboxyl group-containing monomers such as acrylic acid, methacrylic acid, crotonic acid, itaconic acid, fumaric acid, maleic acid, and citraconic acid, and salts thereof; various hydroxyl group-containing monomers such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, monobutyl hydroxyl fumarate, and monobutyl hydroxy itaconate; methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, lauryl (meth)acrylate, and the like. various nitrogen-containing compounds such as (meth)acrylamide, diacetone acrylamide, N-methylol acrylamide, or (meth)acrylonitrile; various styrene derivatives such as styrene, α-methylstyrene, divinylbenzene, or vinyl toluene; various vinyl esters such as vinyl propionate; various silicon-containing polymerizable monomers such as γ-methacryloxypropyltrimethoxysilane, vinyltrimethoxysilane, or the like; phosphorus-containing vinyl monomers; various vinyl halides such as vinyl chloride and vinylidene chloride; and various conjugated dienes such as butadiene.

[0070] The proportion of the compound (C) in the total non-volatile components in the cured resin layer composition is usually 15 to 90 mass%, preferably 45 to 90 mass%, more preferably 60 to 85 mass%. When the proportion of the compound (C) is equal to or less than the upper limit, the proportions of other components are appropriately high, so that insufficient antistatic properties and film-forming properties can be prevented. On the other hand, when the proportion of the compound (C) is equal to or more than the lower limit, insufficient transparency of the cured resin layer can be prevented.

[0071] The thickness of the cured resin layer is not particularly limited, but is preferably 0.002 to 1.0 μm, more preferably 0.005 to 0.25 μm, and even more preferably 0.02 to 0.10 μm. If the thickness of the cured resin layer is within the above range, the function of the cured resin layer, such as antistatic properties, can be adequately exhibited. In addition, the particles blended into the base film make it easier to adjust the maximum cross-sectional height (Rt) of the opposite release surface.

[0072] <Method of forming cured resin layer> Next, a method for forming the cured resin layer will be described. The method for forming the cured resin layer is not particularly limited, and includes a method of applying a cured resin composition to a substrate film, and drying and curing the composition as necessary to form a cured resin layer. The method for applying the cured resin composition is not limited, and any conventionally known coating method such as reverse gravure coating, direct gravure coating, roll coating, die coating, bar coating, curtain coating, etc. can be used. The cured resin layer can be formed by in-line coating or off-line coating. The drying and curing conditions are not particularly limited, and when the cured resin layer is formed by off-line coating, the heat treatment is usually performed at 80 to 200°C for 3 to 40 seconds, preferably at 100 to 180°C for 3 to 40 seconds. On the other hand, when the cured resin layer is provided by in-line coating, it is usually preferable to carry out the heat treatment at 70 to 280° C. for 3 to 200 seconds as a guideline.

[0073] In the present invention, it is preferable to form the film by in-line coating, in which the film surface is treated during the film-forming process of the base film. In the following, an example will be described in which the base film is a polyester film. In-line coating is a method of coating within the polyester film production process, specifically, a method of coating at any stage from melt extrusion of polyester to stretching, heat setting and winding up. Usually, coating is performed on any of the following: an unstretched sheet obtained by melting and quenching, a stretched uniaxially stretched film, a biaxially stretched film before heat setting, or a film after heat setting and before winding up. Although not limited to the following, for example, in the case of sequential biaxial stretching, a method of coating a uniaxially stretched film stretched in the longitudinal direction (machine direction) and then stretching in the transverse direction is particularly excellent. According to such a method, film formation and formation of a cured resin layer can be performed simultaneously, which is advantageous in terms of production costs. In addition, since stretching is performed after coating, the thickness of the cured resin layer can be changed by the stretching ratio, and thin film coating can be performed more easily than with an offline coating film. In addition, by providing a cured resin layer on the film before stretching, the cured resin layer can be stretched together with the polyester film, and thus the cured resin layer can be firmly attached to the polyester film. Furthermore, in the production of a biaxially stretched polyester film, the film can be restrained in the machine direction and the transverse direction by stretching while holding the film end with a clip or the like, and high temperatures can be applied in the heat fixing step while maintaining the flatness without wrinkles or the like. Therefore, the heat treatment performed after coating can be performed at a high temperature that cannot be achieved by other methods, thereby improving the film-forming properties of the cured resin layer and enabling stronger adhesion between the cured resin layer and the polyester film. Furthermore, a stronger cured resin layer can be formed, and performance such as adhesion to various functional layers that can be formed on the cured resin layer and moist heat resistance can be improved.

[0074] When the cured resin layer is provided by in-line coating, it is preferable to produce the substrate film by coating a polyester film with a cured resin layer composition prepared by preparing an aqueous solution or aqueous dispersion of the above-mentioned series of compounds so that the solid content (total non-volatile components) is adjusted to approximately 0.1 to 50 mass %.

[0075] Regardless of whether off-line coating or in-line coating is used, heat treatment and irradiation with active energy rays such as ultraviolet rays may be used in combination as necessary. The polyester film constituting the base film of the present invention may be previously subjected to a surface treatment such as a corona treatment or a plasma treatment.

[0076] <<Release film manufacturing method>> The release film can be produced by forming other layers, such as an antistatic layer or an oligomer sealing layer, on one or both sides of a substrate film, as necessary, and then applying the release layer composition to the surface of the layer and curing the release layer by heat treatment, etc. The applied release layer composition may be appropriately dried by heat treatment.

[0077] The release layer composition can be applied by a conventional coating method such as multi-roll coating, reverse gravure coating, direct gravure coating, bar coating, die coating, etc. Coating methods are described in "Coating Methods" (published by Maki Shoten in 1979 by Yuji Harasaki). The coating amount of the release layer composition, i.e., the thickness of this release layer (after drying), is as described above. Furthermore, the substrate film may be subjected to a surface treatment such as a corona treatment or a plasma treatment before applying the release layer composition.

[0078] When the release layer composed of the applied release layer composition is heat-treated, a conventionally known heat treatment device can be used. For example, a heating oven, a hot plate, a hot air dryer, a near infrared lamp, an air dryer, etc. are exemplified. The heat treatment temperature is, for example, in the range of 35 to 100°C, preferably 40 to 100°C, and more preferably 50 to 100°C. Furthermore, the heat treatment time is, for example, in the range of 3 seconds to 3 minutes, preferably 5 seconds to 2 minutes, and more preferably 5 seconds to 1 minute.

[0079] The release layer formed from the release layer composition applied to the substrate film may be irradiated with ultraviolet light as appropriate. For example, the heat-treated release layer may be subjected to ultraviolet light irradiation treatment. When performing ultraviolet light irradiation treatment, a conventionally known ultraviolet light irradiation device may be used. For example, examples of light sources include fusion (H) lamps, metal halide lamps, high-pressure mercury lamps (ozone generating type, ozone-less type), UV-LEDs, etc.

[0080] The amount of ultraviolet light irradiation is not particularly limited, but is preferably 10 to 3000 (m J / cm) in terms of the cumulative light amount. 2 ), preferably 50 to 2000 (mJ / cm 2 ), more preferably 100 to 1000 (mJ / cm 2 ) range is good.

[0081] <<Release film properties>> The release film may have the following physical properties:

[0082] <Elastic modulus of release layer> In the present invention, the release layer has an elastic modulus of 500 MPa or less at 25° C. The elastic modulus here is a value measured by a nanoindenter. If the elastic modulus is higher than 500 MPa, the release film does not have good peeling properties, and it is difficult to achieve ultra-light peeling. The elastic modulus of the release layer at 25° C. is preferably 400 MPa or less, more preferably 300 MPa or less. The lower limit is preferably 65 MPa or more, more preferably 80 MPa or more. By satisfying these ranges, the easy peelability from the adhesive layer is particularly good. The elastic modulus of the release layer can be adjusted by the type of silicone resin used, the thickness of the release layer, etc. For example, the thinner the release layer, the higher the elastic modulus tends to be.

[0083] <Maximum cross-sectional height of the opposite release surface (Rt)> From the viewpoint of preventing blocking of the release film roll, the maximum cross-sectional height (Rt: μm) of the opposite release surface must be greater than the thickness (μm) of the release layer and equal to or less than 2.0 μm. From the viewpoint of preventing blocking, the maximum cross-sectional height (Rt) of the opposite release surface is preferably 0.6 to 2.0 μm, more preferably 0.9 to 2.0 μm, even more preferably 1.2 to 2.0 μm, still more preferably 1.4 to 2.0 μm, and particularly preferably 1.6 to 2.0 μm. From the viewpoint of preventing blocking, the difference between the maximum cross-sectional height (Rt) of the non-release surface and the thickness of the release layer is more preferably 0.4 μm or more, even more preferably 0.6 μm or more, and particularly preferably 0.8 μm or more. The difference may be 1.8 μm or less, but from the viewpoint of migration, it is preferably 1.5 μm or less, more preferably 1.0 μm or less. When a release film having a thick release layer as in the present invention is wound up into a roll, it is presumed that if the Rt of the anti-release surface is small, the formation of gaps between the release layer and the anti-release surface will be small, the contact area with the anti-release surface will be large, and adhesion will be more likely to occur. However, in the present invention, the Rt of the anti-release surface is set within a specified range, making adhesion less likely, thereby preventing blocking.

[0084] <Normal peel strength> The release film preferably has a normal peel strength of 10 g / inch or less, more preferably 6 g / inch or less, and particularly preferably 4 g / inch or less. The normal peel strength is the peel strength measured when an acrylic adhesive tape (manufactured by Tesa, product name "No. 7475") is attached to the release layer surface of the release film, cut to a size of 50 mm x 300 mm, left at room temperature (23 ° C) for 1 hour, and then peeled at 180 ° measured under the condition of a pulling speed of 0.3 m / min. The release film of the present invention has a low normal peel strength and can obtain ultra-light releasability even during low-speed peeling. The normal peel strength is not particularly limited, but may be, for example, 0.1 g / inch or more, or 0.5 g / inch or more.

[0085] <Heat peel strength> The release film can have a heat peeling force of 12 g / inch or less, preferably 10 g / inch or less, and particularly preferably 8 g / inch or less. The heat peeling force is measured by attaching an adhesive tape (manufactured by Tesa, product name "No. 7475") to the release surface of a sample film, cutting it to a size of 50 mm x 300 mm, and heat-treating it at 100 ° C. for 1 hour in a hot air oven. Thereafter, the sample is taken out and left at room temperature for 1 hour, and the 180 ° peeling force is measured under the condition of a pulling speed of 0.3 m / min. The release film of the present invention has a low heat peeling force and can maintain ultra-light peelability even when used at high temperatures. The heat peeling force is not particularly limited, but may be, for example, 0.1 g / inch or more, or 1 g / inch or more.

[0086] <Residual adhesion rate> As described above, it is preferable that the release film has low migration property, and the residual adhesion rate (%) is an index of this property. The details of the method for measuring the residual adhesion rate are as described in the Examples. The residual adhesion rate (%) is an index showing the degree to which the release agent migrates to the evaluation film when the evaluation film is overlapped and pressed on the release layer surface of the release film. In the case of a release film with high migration, a lot of silicone adheres to the overlapped evaluation film, so the peeling force of the adhesive tape attached to the evaluation film becomes small, and the residual adhesion rate (%) also decreases. Therefore, it is preferable that the release film has a high residual adhesion rate (%), specifically, 90% or more is preferable, 92% or more is more preferable, and among them, 94% or more is particularly preferable.

[0087] <<Release film with adhesive layer>> The release film with an adhesive layer of the present invention comprises the above-mentioned release film and an adhesive layer laminated on the surface of the release film on the release layer side. The adhesive layer is formed from an adhesive composition.

[0088] <Adhesive composition> The pressure-sensitive adhesive composition may be an acrylic-based pressure-sensitive adhesive composition having an acrylic resin as the main component resin, a rubber-based pressure-sensitive adhesive composition having rubber as the main component, a urethane-based pressure-sensitive adhesive composition having a urethane resin as the main component, or a silicone-based pressure-sensitive adhesive composition having a silicone resin as the main component. Among them, the pressure-sensitive adhesive composition is preferably an acrylic pressure-sensitive adhesive composition containing an acrylic resin as a main component, because the adhesive strength and peel strength can be adjusted in a well-balanced manner and the pressure-sensitive adhesive composition is inexpensive.

[0089] The above-mentioned "main component resin" means a resin having the highest mass ratio among the resins constituting the adhesive composition. For example, it means a component that occupies 50 mass% or more, preferably 60 mass% or more, more preferably 70 mass% or more of the total amount of resins constituting the adhesive composition. The upper limit is 100 mass%, but is usually 99.99 mass%.

[0090] The adhesive composition may contain, other than the main component, a crosslinking agent described below, and, if necessary, a resin (e.g., an acrylic resin, a rubber, a silicone resin, a urethane resin) that constitutes an adhesive component other than the main component resin. In addition, additives such as tackifiers such as rosin, rosin esters, hydrogenated rosin esters, phenolic resins, aromatic modified terpene resins, aliphatic petroleum resins, alicyclic petroleum resins, styrene-based resins, and xylene-based resins, silane coupling agents, antistatic agents, colorants, fillers, antioxidants, ultraviolet absorbers, and functional dyes, as well as additives such as compounds that undergo coloring or discoloration upon exposure to ultraviolet light or radiation, can be blended. The blending amount of these additives is preferably 10% by mass or less of the entire pressure-sensitive adhesive composition (based on non-volatile components), more preferably 5% by mass or less, and particularly 5% by mass or less, and it is preferable that additives contain as few low-molecular-weight components having a molecular weight of less than 10,000 as possible in terms of excellent durability.

[0091] (Acrylic resin) The acrylic resin that is the main component resin of the pressure-sensitive adhesive composition may be a (meth)acrylic polymer.

[0092] The (meth)acrylic polymer is a polymer having a (meth)acrylic acid alkyl ester as a main constituent unit. Examples of (meth)acrylic acid alkyl esters include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, t-butyl (meth)acrylate, n-pentyl (meth)acrylate and n-hexyl (meth)acrylate, isobornyl (meth)acrylate, 4-t-butylcyclohexyl (meth)acrylate, tricyclodecanyl (meth)acrylate, dicyclopentaenyl (meth)acrylate, and adamantyl (meth)acrylate. These may be used alone or in combination of two or more. Among these, methyl (meth)acrylate is preferred from the viewpoints of compatibility with other (meth)acrylates constituting the (meth)acrylic polymer and heat resistance of the cured resin layer. The content of the (meth)acrylic acid alkyl ester (a2) in the monomers forming the (meth)acrylic polymer is, for example, 50 mass% or more, preferably 60 to 99.99 mass%, more preferably 75 to 98.9 mass%, and even more preferably 87 to 97.8 mass%. The (meth)acrylic polymer may have a radically polymerizable double bond.

[0093] For the purpose of improving the glass transition temperature, mechanical properties, compatibility, etc., the (meth)acrylic polymer can be copolymerized with (meth)acrylic acid esters other than (meth)acrylic acid alkyl esters, (meth)acrylic acid, and other compounds having a vinyl group. Examples of (meth)acrylic acid esters other than the (meth)acrylic acid alkyl esters that can be used as copolymerization components include (meth)acrylic acid alkoxyalkyl esters such as hydroxyalkyl (meth)acrylate, methoxymethyl (meth)acrylate, methoxyethyl (meth)acrylate, ethoxymethyl (meth)acrylate, and ethoxyethyl (meth)acrylate, as described below, phenyl (meth)acrylate, benzyl (meth)acrylate, glycidyl (meth)acrylate, and γ-butyrolactone (meth)acrylate. Examples of the compound having a vinyl group include acrylamide compounds such as dimethylacrylamide, hydroxyethylacrylamide, and dimethylaminopropylacrylamide; styrene compounds such as styrene, α-methylstyrene, and p-methoxystyrene; and maleic anhydride. In addition, components (a1) and (a2) described below can also be used appropriately.

[0094] The glass transition temperature (Tg) can be calculated from the type and mass fraction of the monomers forming the (meth)acrylic polymer by the following Fox formula. 1 / Tg=Σ(Wi / Tgi) In this formula, Tg is the glass transition temperature (unit: K) of the (meth)acrylic polymer, W is the mass fraction of the monomer unit derived from monomer i constituting the (meth)acrylic polymer, and Tgi is the glass transition temperature (unit: K) of the homopolymer of monomer i. The value of Tgi can be the value described in POLYMERHANDBOOK Volume 1 (WILEY-INTERSCIENCE).

[0095] In the present invention, the monomer constituting the (meth)acrylic polymer may contain, in addition to the (meth)acrylic acid alkyl ester, an acrylic monomer (a1) as a copolymerization component, which serves as a reaction site with the crosslinking agent described below.

[0096] The acrylic monomer (a1) is a reactive site of a crosslinking structure when it is copolymerized with other copolymerization components to form an acrylic resin, and a monomer containing a functional group capable of reacting with a functional group contained in the crosslinking agent (B) described later may be used. Examples of such acrylic monomer (a1) include hydroxyl group-containing monomers, amino group-containing monomers, acetoacetyl group-containing monomers, isocyanate group-containing monomers, and glycidyl group-containing monomers. Among these, hydroxyl group-containing monomers are preferably used because they can efficiently crosslink with the crosslinking agent. The acrylic monomer (a1) may be used alone or in combination of two or more kinds.

[0097] Examples of hydroxyl group-containing monomers include acrylic acid hydroxyalkyl esters such as 2-hydroxyethyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 5-hydroxypentyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, and 8-hydroxyoctyl (meth)acrylate; caprolactone-modified monomers such as caprolactone-modified 2-hydroxyethyl (meth)acrylate; oxyalkylene-modified monomers such as diethylene glycol (meth)acrylate and polyethylene glycol (meth)acrylate; and primary hydroxyl group-containing monomers such as 2-acryloyloxyethyl 2-hydroxyethyl phthalate and N-methylol (meth)acrylamide; secondary hydroxyl group-containing monomers such as 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, and 3-chloro 2-hydroxypropyl (meth)acrylate; and tertiary hydroxyl group-containing monomers such as 2,2-dimethyl 2-hydroxyethyl (meth)acrylate.

[0098] Among the above hydroxyl group-containing monomers, primary hydroxyl group-containing monomers are preferred because of their excellent reactivity with crosslinking agents. Furthermore, the use of 2-hydroxyethyl acrylate is particularly preferred because it contains less impurities such as di(meth)acrylates and is easy to produce.

[0099] In addition, as the hydroxyl group-containing monomer used in the present invention, it is also preferable to use one having a content of di(meth)acrylate as an impurity of 0.5% by mass or less, more preferably 0.2% by mass or less, and particularly preferably 0.1% by mass or less. Specifically, as the hydroxyl group-containing monomer, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, 4-hydroxybutyl acrylate, etc. are particularly preferable, and these are preferable in that they have a low molecular weight and are easy to purify.

[0100] Examples of the amino group-containing monomer include t-butylaminoethyl (meth)acrylate, ethylaminoethyl (meth)acrylate, dimethylaminoethyl (meth)acrylate, and diethylaminoethyl (meth)acrylate.

[0101] Examples of acetoacetyl group-containing monomers include 2-(acetoacetoxy)ethyl (meth)acrylate and allyl acetoacetate.

[0102] Examples of the isocyanate group-containing monomer include 2-acryloyloxyethyl isocyanate, 2-methacryloyloxyethyl isocyanate, and alkylene oxide adducts thereof.

[0103] Examples of the glycidyl group-containing monomer include glycidyl (meth)acrylate and allyl glycidyl (meth)acrylate.

[0104] The content of the acrylic monomer (a1) in the monomers constituting the (meth)acrylic polymer is preferably from 0.01 to 20 mass %, more preferably from 0.1 to 10 mass %, and even more preferably from 0.2 to 3 mass %. When the acrylic monomer (a1) is at or above the lower limit, the crosslinking points during crosslinking are appropriate, resulting in good cohesive strength after crosslinking. When the acrylic monomer (a1) is at or below the upper limit, a decrease in adhesive strength due to the (a1) component can be prevented.

[0105] Furthermore, the monomer constituting the (meth)acrylic polymer may contain, in addition to the (meth)acrylic acid alkyl ester, or the (meth)acrylic acid alkyl ester and the component (a1), a copolymerizable monomer (a2) other than (a1) as a copolymerization component, as necessary. Examples of the copolymerizable monomer (a2) include aromatic ring-containing monomers such as phenyl(meth)acrylate, benzyl(meth)acrylate, phenoxyethyl(meth)acrylate, ethoxylated o-phenylphenyl(meth)acrylate, phenoxydiethylene glycol(meth)acrylate, 2-hydroxy-3-phenoxypropyl(meth)acrylate, and styrene; amide monomers such as (meth)acryloylmorpholine, dimethyl(meth)acrylamide, diethyl(meth)acrylamide, and (meth)acrylamide; acrylonitrile, methacrylonitrile, vinyl acetate, vinyl propionate, vinyl stearate, vinyl chloride, vinylidene chloride, alkyl vinyl ethers, vinyl toluene, vinyl pyridine, vinyl pyrrolidone, dialkyl itaconic acid esters, dialkyl fumaric acid esters, allyl alcohol, acrylic chloride, methyl vinyl ketone, N-acrylamidomethyltrimethylammonium chloride, allyltrimethylammonium chloride, and dimethylallyl vinyl ketone.

[0106] The content of the copolymerizable monomer (a2) in the monomers forming the (meth)acrylic polymer is preferably 0 to 20 mass%, more preferably 1 to 15 mass%, and particularly preferably 2 to 10 mass%. When the content of the copolymerizable monomer (a2) is within the above range, a decrease in adhesive properties can be prevented.

[0107] (Crosslinking agent) The pressure-sensitive adhesive composition may contain a crosslinking agent as necessary depending on the curing method. Examples of the crosslinking agent include an isocyanate-based crosslinking agent, an epoxy-based crosslinking agent, an aziridine-based crosslinking agent, a melamine-based crosslinking agent, an aldehyde-based crosslinking agent, an amine-based crosslinking agent, etc. Among them, an isocyanate-based crosslinking agent is preferably used in terms of improving adhesion to the substrate or reactivity with the acrylic resin. The crosslinking agents may be used alone or in combination of two or more kinds.

[0108] The content of the crosslinking agent is preferably 0.01 to 10 parts by mass, more preferably 0.05 to 5 parts by mass, and even more preferably 0.1 to 3 parts by mass, relative to 100 parts by mass of the main component resin. If the content of the crosslinking agent is within the above range, the cohesive strength is not insufficient and the desired durability can be obtained, while a decrease in flexibility and adhesive strength can be prevented.

[0109] In addition, when the curing reaction is photocuring by irradiation with active energy rays, it is preferable to mix a polyfunctional (meth)acrylate into the adhesive composition as a crosslinking agent. Examples of such polyfunctional (meth)acrylates include trimethylolpropane tri(meth)acrylate, ethylene oxide modified trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, and glycerin polyglycidyl ether poly(meth)acrylate.

[0110] The adhesive layer may be formed by applying the adhesive composition onto the release layer of the release film, followed by drying and curing as appropriate. The adhesive composition may be cured depending on the crosslinking agent and main component resin, and may be cured by heating or by irradiation with light such as ultraviolet light. The adhesive composition may be applied onto the release layer after being appropriately diluted with an organic solvent or the like.

[0111] <Adhesive layer thickness> The thickness of the adhesive layer is not particularly limited. For example, from the viewpoint of imparting sufficient adhesive strength and filling unevenness or steps of the substrate to which the adhesive is attached, it is preferably 0.1 μm or more, more preferably 0.5 μm or more, and even more preferably 1 μm or more. On the other hand, from the viewpoint of material use efficiency, permeability, and outgassing, it is preferably 10000 μm or less, more preferably 3000 μm or less, and even more preferably 1000 μm or less.

[0112] <Elastic modulus of adhesive layer> In the present invention, the adhesive layer preferably has a modulus of elasticity of 15 MPa or more at 25°C. With a modulus of elasticity of 15 MPa or more, the adhesive layer has good durability. From these viewpoints, the modulus of elasticity of the adhesive layer is more preferably 20 MPa or more, and even more preferably 25 MPa or more. Moreover, from the viewpoint of conformability to the adherend, the modulus of elasticity of the adhesive layer at 25°C is preferably 100 MPa or less, more preferably 80 MPa or less, and even more preferably 60 MPa or less. The elastic modulus of the pressure-sensitive adhesive layer is measured at room temperature (25° C.) using a nanoindenter.

[0113] <<<Film laminate>>> The release film with the adhesive layer can be used for various film laminates. For example, the release film with the adhesive layer can be used to prepare a film laminate having a configuration in which an optical member is attached to the surface of the adhesive layer. By peeling off the release film, the optical member can be attached to the adherend by the exposed adhesive layer. Examples of the optical member include a polarizing plate, a touch sensor, etc. The optical member may also be an in-vehicle optical member such as a touch panel mounted on an automobile.

[0114] (Polarizing plate) The polarizing plate may be made of any material and have any structure. For example, a polarizing plate of this type is widely used in which a TAC (triacetyl cellulose) film is laminated as a protective film on a stretched polyvinyl alcohol film using iodine as an orientation dye. The polarizing plate may have a layer structure on the surface that has a hard coat having substantially no phase difference, antiglare, low reflection, antistatic, or other functions.

[0115] (Touch Sensor) The touch sensor is a component that detects the touched point when a user touches an image displayed on a screen with a finger or a touch pen, and depending on the sensor technology, examples include a capacitive type, a resistive film type, and a surface wave type using infrared rays or ultrasound. Touch sensors are generally installed in display devices such as liquid crystal display panels and organic electroluminescence (EL) displays. Furthermore, in recent years, there has been a trend to use base films as an alternative to glass substrates, focusing on their flexibility, and it is preferable to use a touch sensor film. Touch sensor films typically include a patterned transparent conductive layer to perform the function of a sensing electrode.

[0116] The film laminate may have a layer structure including the release film with the adhesive layer and another release film, and the release film with the adhesive layer is bonded to the other release film via the adhesive layer. The film laminate having such a layer structure has a structure of the release film / adhesive layer / other release film, and can be used as a double-sided adhesive sheet. The other release film is a film in which a release layer is formed on the surface of a substrate such as a resin film, and the surface on which the release layer is formed is preferably attached to the adhesive layer. The release layer of the other release film may be any other layer than the above-mentioned release layer.

[0117] In the film laminate having the above structure, the ratio (MB / MA) of the modulus of elasticity (MA) of the release layer of the present release film to the modulus of elasticity (MB) of the release layer of the other release film is preferably in the range of 4 to 30, more preferably in the range of 4 to 25. When the modulus of elasticity falls within the above range, it is possible to reduce the problem of the present release film peeling off in situations where peeling is not actually required in the film laminate.

[0118] The film laminate to which the other release film is attached may be used by peeling off the release film and attaching the exposed adhesive layer surface of the remaining release film with adhesive layer to an optical member. Then, the other release film may be peeled off from the adhesive layer of the release film with adhesive layer. Also, the release film may be attached again to the adhesive layer attached to the optical member after that. In this way, the release film of the present invention has an extremely light peelability and low migration property, so it is possible to use the so-called release film by peeling it off again.

[0119] The normal peel strength of the other release film, measured at a peel speed of 0.3 m / min and 180° peeling, is greater than that of the present release film, and specifically is preferably about 2 to 10 times, and more preferably 2 to 6 times, the normal peel strength of the present release film. By satisfying the above-mentioned peel strength ratio, it is possible to reduce the problem of the present release film peeling off in situations where peeling is not actually required.

[0120] The release film and film laminate described above are preferably used for vehicle mounting. When used for vehicle mounting, it is necessary to increase the adhesive strength of the adhesive layer in order to maintain high adhesive strength even when exposed to a high temperature atmosphere in summer or a low temperature environment in winter. Since this release film can realize super-light peeling property, the peeling performance is good even if the adhesive strength of the adhesive layer is high.

[0121] <<<Explanation of terms, etc.>>> In the present invention, the term "film" includes the term "sheet", and the term "sheet" includes the term "film". Furthermore, when the term "panel" is used, such as an image display panel, a protective panel, a touch panel, etc., it encompasses a plate, a sheet, and a film.

[0122] In the present invention, when it is described as "X to Y" (X and Y are any numbers), unless otherwise specified, it includes the meaning of "X or more and Y or less", as well as the meaning of "preferably larger than X" or "preferably smaller than Y". In addition, when it is stated that the amount is "X or more" (X is any number), it also means that the amount is "preferably greater than X" unless otherwise specified, and when it is stated that the amount is "Y or less" (Y is any number), it also means that the amount is "preferably smaller than Y" unless otherwise specified. EXAMPLES

[0123] The present invention will now be described in more detail with reference to examples, although the present invention is not limited to the examples described below.

[0124] <Evaluation method> As described below, the release film was used as a sample film and various physical properties were measured and evaluated as follows.

[0125] (1) Release layer thickness measurement To suppress reflection from the back side, black tape (Vinyl Tape VT-50, manufactured by Nichiban Co., Ltd.) was applied to the back side of the sample film beforehand. For the measurement, a spectrophotometer (UV-Visible Spectrophotometer V-670, manufactured by JASCO Corporation) was used to measure the absolute reflectance in the wavelength range of 300 to 800 nm under the following conditions: synchronous mode, incident angle 5°, N polarization, response Fast, data acquisition interval 1.0 nm, bandwidth 10 nm, and scanning speed 1000 m / min. The film thickness was calculated by comparing the data obtained from this measurement with the data calculated assuming the refractive index of silicone to be 1.43. (2) Maximum section height (Rt) The maximum cross-sectional height (Rt) of the opposite release surface was measured using a surface roughness meter conforming to JIS B 0601-2001 (two-dimensional roughness meter "surfcorder SE3500" manufactured by Kosaka Laboratory Co., Ltd.). Rt can be calculated as the sum of the maximum peak height Rp and the maximum valley depth Rv of the roughness curve in the evaluation length. (3) Normal peel strength The release layer of the sample film was pressed (twice back and forth) with a rubber roller (2 kg), and adhesive tape (Tesa's "No. 7475") was attached, then cut to a size of 50 mm x 300 mm and left at room temperature (23°C) for 1 hour, after which the peel strength was measured. The peel strength was measured using Intesco's "Intesco Model 2001" at a tensile speed of 0.3 m / min, with the sample film peeled at 180°. (Judgment criteria) The peelability of the sample film was evaluated based on the measured normal peel force and in accordance with the following criteria. A(good): 10g / inch or less B(poor):Over 10g / inch

[0126] (4) Heat peeling strength The release layer surface of the sample film was pressed (2 times back and forth) with a rubber roller (2 kg), and an adhesive tape (Tesa "No. 7475") was attached, then the film was cut to a size of 50 mm x 300 mm and heat-treated at 100°C for 1 hour in a hot air oven. The sample film was then removed from the oven and left at room temperature for 1 hour, after which the peel force was measured. The peel force was measured using Intesco Model 2001 manufactured by Intesco Co., Ltd., and the sample film was peeled at 180° under the condition of a tensile speed of 0.3 (m / min). The lower the value of the heat peel force, the better.

[0127] (5) Adhesive peel strength The adhesive composition below was applied to the release layer surface of the sample film so that the film thickness in a wet state was 2 mil, and the composition was cured by heating at 150°C for 3 minutes to form an adhesive layer (thickness (after drying) 20 μm). The elastic modulus of the resulting adhesive layer was 20 MPa. The elastic modulus of the adhesive layer was measured at room temperature (25°C) using a nanoindenter (TI 950 Tribo Indenter) manufactured by Hysitron.

[0128] <<Adhesive composition>> Base material (acrylic resin): AT352 (manufactured by Saiden Chemical) 100 parts by weight Crosslinking agent: AL (manufactured by Saiden Chemical) 0.25 parts by mass Additive: X-301-375SK (manufactured by Saiden Chemical) 0.25 parts by weight Additive: X-301-352S (manufactured by Saiden Chemical) 0.25 parts by weight Toluene: 40 parts by weight

[0129] Thereafter, another release film was laminated on the adhesive layer to obtain a film laminate consisting of the sample film / adhesive layer / another release film. Note that as the other release film, the release film produced in Comparative Example 1 described below was used. The peel strength of the obtained film laminate was measured when peeling the sample film from the adhesive layer. The peel strength was measured using an Intesco Model 2001 manufactured by Intesco Co., Ltd., at a tensile speed of 0.3 m / min and a 180° peel angle.

[0130] (6) Elastic modulus of release layer The elastic modulus of the release layer was measured at a pressing depth of 50 nm at room temperature (25° C.) using a nanoindenter (TI 950 TriboIndenter) manufactured by Hysitron.

[0131] (7) Residual adhesion rate of release layer The sample film was cut to A4 size (210 mm × 297 mm), and a 75 μm thick biaxially stretched PET film (Diafoil T100-75, manufactured by Mitsubishi Chemical Corporation) was placed on the release layer surface and pressed at a temperature of 60° C. and a pressure of 1 MPa for 2 hours. The "75 μm thick biaxially stretched PET film" alone was used as the evaluation film. On the other hand, an untreated base film was prepared in the same manner as the release film except that no release layer was provided, and the same "75 μm thick biaxially oriented PET film" as above was placed on top of it and pressed under the same conditions as above, and the "75 μm thick biaxially oriented PET film" alone was used as the reference film. The evaluation film and the reference film were pressed (twice back and forth) with a rubber roller (2 kg), and adhesive tape ("No. 31B" manufactured by Nitto Denko Corporation) was attached to the evaluation film and the reference film, and then cut to a size of 50 mm x 300 mm and left at room temperature for 1 hour, after which the peel strength was measured. The adhesive tape was attached to the surfaces of the evaluation film and the reference film that had been in contact with the sample film and the base film, respectively. The peel strength was measured using an Intesco Model 2001 manufactured by Intesco Corporation, with the evaluation film and the reference film each being peeled off at 180° at a tensile speed of 0.3 m / min. The measured peel strength of the evaluation film and the peel strength of the reference film were then substituted into the following formula to calculate the residual adhesion rate (%). Residual adhesion rate (%) = (peel strength of evaluation film / peel strength of reference film) x 100

[0132] With films with high migration, a lot of silicone adheres to the overlapping film, reducing the peeling strength of the adhesive tape and decreasing the residual adhesion rate (%). Therefore, the migration of release films was evaluated according to the residual adhesion rate as follows: (Judgment criteria) A(very good): 94% or more B(good): 90% or more but less than 94% C(poor): Less than 90%

[0133] (8) Adhesion between the base film and the release layer The sample film was left in a thermo-hygrostat at 60°C and 80% RH for 4 weeks, and then removed. The release layer surface of the sample film was rubbed with a feeler five times, and the adhesion was evaluated according to the degree of peeling of the release layer according to the following evaluation criteria. Evaluation Criteria A (very good): No peeling of the coating was observed. B (good): The coating film turned white but did not fall off. C (poor): Paint film peeling was observed.

[0134] (9) Blocking property evaluation The release films of the Examples and Comparative Examples were arranged so that the release layer surface and the non-release surface faced each other, and pressed with a press at a pressure of 10 kg / cm. 2 The sample was subjected to pressure for 20 hours under an atmosphere of 40°C and 80% RH to obtain a measurement sample for evaluating blocking resistance. Thereafter, the peeling force was measured using a peeling device ("AGI" manufactured by Shimadzu Corporation) under conditions of a pulling speed of 300 mm / min and 180° peeling, and the peeling force at this time was used as an index of blocking resistance. Note that the smaller the peeling force, the better the blocking resistance is judged to be. Evaluation Criteria A (good): The peeling force is 20 g / inch or less, and peeling is possible without any problems. B (poor): The peel force exceeds 20 g / inch, causing blocking.

[0135] (10) Overall rating The peelability, migration, blocking resistance, and adhesion were evaluated according to the following criteria. (Judgment criteria) A: Peelability, migration, blocking, and adhesion were all rated A. B: Of the peelability, migration, blocking, and adhesion properties, only migration was rated B and the rest were rated A. C: Any one of peelability, migration, blocking, and adhesion was rated C; or any one of peelability, blocking, and adhesion was rated B.

[0136] [Raw materials] The following raw materials were used in the examples and comparative examples.

[0137] <Production method of polyester (1)> 100 parts by mass of dimethyl terephthalate and 55 parts by mass of ethylene glycol were used as starting materials, and 0.04 parts by mass of magnesium acetate tetrahydrate was added to the reactor as a catalyst. The reaction was started at 150°C, and the reaction temperature was gradually increased as methanol was distilled off, reaching 230°C after 3 hours. After 4 hours, the transesterification reaction was essentially completed. 0.02 parts by mass of ethyl acid phosphate was added to this reaction mixture, and then 0.04 parts by mass of antimony trioxide was added, and the polycondensation reaction was carried out for 4 hours. That is, the temperature was gradually increased from 230°C to 280°C. Meanwhile, the pressure was gradually reduced from normal pressure, and finally reached 0.3 mmHg. After the start of the reaction, the reaction was stopped at the point corresponding to an intrinsic viscosity of 0.59 dl / g due to a change in the stirring power of the reaction vessel, and the polymer was discharged under nitrogen pressure to obtain polyester (1) with an intrinsic viscosity of 0.59 dl / g.

[0138] <Production method of polyester (2)> 100 parts by mass of dimethyl terephthalate and 45 parts by mass of ethylene glycol were used as starting materials, and 0.06 parts by mass of magnesium acetate tetrahydrate was added to the reactor as a catalyst. The reaction was started at 150°C, and the reaction temperature was gradually increased as methanol was distilled off, reaching 230°C after 3 hours. After 4 hours, the transesterification reaction was essentially completed. 0.03 parts by mass of ethyl acid phosphate was added to this reaction mixture, and then 0.3 parts by mass of silica particles with an average particle size of 2.7 μm dispersed in ethylene glycol and 0.03 parts by mass of antimony trioxide were added, and the polycondensation reaction was carried out for 4 hours. That is, the temperature was gradually increased from 230°C to 280°C. Meanwhile, the pressure was gradually reduced from normal pressure, and finally reached 0.3 mmHg. After the start of the reaction, the reaction was stopped at the point corresponding to an intrinsic viscosity of 0.59 dl / g due to changes in the stirring power of the reaction vessel, and the polymer was discharged under nitrogen pressure to obtain polyester (2) with an intrinsic viscosity of 0.59 dl / g.

[0139] <Production method of polyester (3)> Polyester (3) having an intrinsic viscosity of 0.60 was obtained in the same manner as polyester (2), except that 10 parts by mass of organic particles (styrene-divinylbenzene: styrene-based resin) having an average particle size of 4.5 μm were added instead of the silica particles in polyester (2).

[0140] <Production method of polyester film> [PET-A] A blend of polyester (1) and polyester (2) in a mass ratio of 82 / 18 was used as the raw material for layer A, and polyester (1) alone was used as the raw material for layer B. The layers were fed into an extruder, heated and melted at 285°C, and the layer A was divided into two parts to form the outermost layer (surface layer), and the layer B was used as the middle layer, resulting in a layer structure of two types of three layers (A (layer A) / B (layer B) / A (layer C)), with a thickness composition ratio of A / B / A=5 / 90 / 5 under the extrusion conditions. The film was cooled and solidified while being in close contact with a mirror-finished cooling drum with a surface temperature of 40-50°C, to produce an unstretched polyethylene terephthalate film. The film was stretched 3.0 times in the longitudinal direction while passing through a group of heating rolls at 85°C, to produce a uniaxially oriented film. The cured resin layer composition shown below was applied to both sides of this uniaxially stretched film, and then the film was introduced into a tenter stretching machine and stretched 4.1 times in the width direction at 100°C. After further heat treatment at 235°C, a 2% relaxation treatment was performed in the width direction to obtain a 50 μm thick biaxially oriented polyester film (PET-A) with a cured resin layer with a film thickness (after drying) of 0.05 μm on both sides.

[0141] (Cured resin layer composition) (A): Thiophene-based antistatic agent Agfa-Gevaert's "Orgacon ICP1010", a conductive agent made of polyethylenedioxythiophene and polystyrene sulfonic acid, was neutralized with concentrated ammonia water to a pH of 9. (B) Polyhydroxy Compounds Polyglycerol with an average degree of polymerization of 4 (C) Aqueous dispersion of a polyester resin having a condensed polycyclic structure copolymerized in the following composition: Monomer composition: (acid component) 2,6-naphthalenedicarboxylic acid / 5-sodium sulfoisophthalic acid / (diol component) ethylene glycol / diethylene glycol = 92 / 8 / / 80 / 20 (mol%) A / B / C=7 / 10 / 83 (mass%)

[0142] [PET-B]~[PET-D] As shown in Table 1 below, PET-B to PET-D were obtained by producing them in the same manner as PET-A, except that the blending of the polyester raw materials was different.

[0143] [Table 1]

[0144] <Release Layer Composition> a1: Curable silicone resin (a silicone resin in which vinyl groups have been introduced to the side chains and / or ends of the main chain consisting of siloxane bonds, number average molecular weight: 10600, viscosity at 25°C when adjusted to 15% by mass with n-heptane solvent: 1.7mcps) a2: Curable silicone resin (a mixture containing a silicone resin (number average molecular weight: 364,000) in which vinyl groups have been introduced to the side chains and / or ends of the main chain consisting of siloxane bonds, and a crosslinking agent in which Si-H groups have been introduced to the side chains and / or ends of the main chain consisting of siloxane bonds (viscosity: 410 mcps at 25°C when adjusted to 15% by mass with n-heptane solvent))

[0145] (Composition analysis of curable silicone resin) Composition analysis of the curable silicone resins used in the examples and comparative examples was performed using a 400 MHz-NMR (Bruker Avance400M), and the results are shown in Table 2. 1H-NMR measurements were performed at a temperature of 30°C using CDCl3 as the solvent and the peak derived from the methyl group of dimethylsiloxane as the chemical shift standard. Table 2 below shows the content (mol%) of each functional group in the curable silicone resin.

[0146] [Table 2]

[0147] b1: Crosslinker (CL750: manufactured by Momentive Performance Materials) c1: Addition type platinum catalyst (PL-50T: Shin-Etsu Chemical Co., Ltd.) c2: Addition-type platinum catalyst (CM678: Momentive Performance Materials)

[0148] [Example 1] The release layer composition described below was applied to the flat surface of the A layer side of the PET-C in an amount (after drying) of 1 g / m 2 After coating so that the coating solution was thickened, the coating solution was dried at 150° C. for 30 seconds to obtain a release film (sample film).

[0149] (Release Layer Composition) Base agent: a1 100 parts by weight Crosslinking agent: b1 3 parts by weight Catalyst: 3 parts by mass of c2 Solvent: toluene 1000 parts by weight MEK 9000 parts by mass

[0150] [Examples 2 to 9] Manufacture was performed in the same manner as in Example 1, except that the thickness of the release layer and the combination of the base film were changed as shown in Tables 3 and 4 below, to obtain a film laminate.

[0151] [Comparative Example 1] A film laminate was obtained in the same manner as in Example 1, except that the release layer composition was changed to the release layer composition shown below. (Release Layer Composition) Base ingredient: A2 100 parts by mass Catalyst: c1 1 part by mass Solvent: toluene 200 parts by weight MEK 200 parts by mass Hexane 200 parts by mass

[0152] [Comparative Example 2] A release film (sample film) was obtained in the same manner as in Example 1, except that the composition of the release layer in Example 1 was changed to the release layer composition shown below.

[0153] (Release Layer Composition) Base agent: a1 100 parts by weight Crosslinking agent: b1 3 parts by weight Catalyst: 3 parts by mass of c2 Particles: Momentive's "Tospearl 120" (average particle size 2 μm) 0.15 parts by mass Solvent: toluene 1000 parts by weight MEK 9000 parts by mass

[0154] [Comparative Example 3] A release film (sample film) was obtained in the same manner as in Example 1, except that the type of base film in Example 1 was changed to PET-A.

[0155] [Table 3] [Table 4]

[0156] From this embodiment and the results of tests conducted by the inventors thus far, it has been found that by making the release layer containing a curable silicone resin relatively thick and setting the elastic modulus to 500 MPa or less, while keeping the maximum cross-sectional height (Rt) of the opposite release surface within a specified range, it is possible to obtain a release film that not only has a light peel force, but also has low migration and is less prone to blocking, and yet still has good adhesion to the substrate. When comparing Comparative Example 1 with each Example in terms of the peel strength (normal peel strength) of the adhesive tape, the lightest type achieved a peel strength that was 1 / 5 of that of Comparative Example 1, thereby achieving an ultra-light peel strength. In contrast, Comparative Example 1 was at the conventional product level (light release type), and it was found that the peeling force to the adhesive layer was large and the adhesion of the release layer to the base film was insufficient. In Comparative Example 2, the release layer itself was brittle, probably because it contained particles in the release layer, and the adhesion to the base film was insufficient. Furthermore, the release layer was highly mobile. In addition, in Comparative Example 3, although there was an effect of making the release easier, it was found that the surface roughness (Rt) of the non-release surface of the base film was insufficient, and therefore the blocking resistance was reduced.

Claims

1. A substrate film and a release layer provided on one side of the substrate film, the release layer contains a curable silicone resin having a vinyl group introduced into a side chain and / or an end of a main chain consisting of a siloxane bond, has a thickness of 0.2 to 1.5 μm, the release layer has an elastic modulus of 500 MPa or less at 25° C. at an indentation depth of 50 nm as measured by a nanoindenter, and has a particle content of less than 0.05% by mass; A release film, wherein the maximum cross-sectional height (Rt) of the film surface opposite to the surface on which the release layer is provided is greater than the thickness (μm) of the release layer and is 2.0 μm or less.

2. The release film according to claim 1, wherein the surface of the base film opposite to the surface on which the release layer is provided is provided with a polyester layer containing 0.4 to 1.0 mass % of particles having an average particle size of 1 to 6 μm.

3. The release film according to claim 1 , further comprising a cured resin layer between the release layer and the base film.

4. The release film according to claim 3 , wherein the cured resin layer is an antistatic layer.

5. The release film according to claim 3 or 4, wherein the cured resin layer is formed by curing a cured resin layer composition containing the following compounds (A) to (C): (A) A polymer in which a compound made of thiophene or a thiophene derivative is doped with another anionic compound, or a self-doped polymer having an anionic group in a compound made of thiophene or a thiophene derivative. (B) Polyhydroxy Compound (C) One or more compounds selected from the group consisting of polyurethane resins, polyester resins, and acrylic resins.

6. The release film according to any one of claims 1 to 5, wherein the base film is a polyester film.

7. The release film according to claim 6 , wherein the polyester film has a three-layer structure.

8. The release film according to any one of claims 1 to 7, wherein an acrylic adhesive tape ("No. 7475" manufactured by Tesa) is attached to the surface of the release film on which the release layer is to be provided, the tape is cut to a size of 50 mm x 300 mm, and the tape is left at room temperature for 1 hour. The release film has a peel strength of 10 g / 2.54 cm or less when peeled at 180° under conditions of a tensile speed of 0.3 m / min.

9. The release film according to any one of claims 1 to 8, which is a release film roll wound in a roll shape.

10. The release film according to any one of claims 1 to 9, which is for in-vehicle use.

11. A film laminate comprising: the release film according to any one of claims 1 to 10; an adhesive layer laminated on the release layer side of the release film; and another release film bonded to the adhesive layer.

12. The film laminate according to claim 11 , wherein the pressure-sensitive adhesive layer is formed from an acrylic pressure-sensitive adhesive composition.

13. The film laminate according to claim 11 or 12, wherein the adhesive layer has an elastic modulus at 25°C of 20 MPa or more and 100 MPa or less.

14. The film laminate according to any one of claims 11 to 13, which is for mounting on a vehicle.

15. A method for using the film laminate according to any one of claims 11 to 14, comprising peeling off the release film according to any one of claims 1 to 10, and then bonding the exposed pressure-sensitive adhesive layer surface to an optical member.

16. The method for using the film laminate according to claim 15, wherein the optical component is a polarizing plate or a touch sensor.

Citation Information

Patent Citations

  • Release film

    JP2004255704A

  • Release film

    JP2011201118A

  • Base-less double-sided tacky adhesive sheet

    JP2013001817A

  • Sheet for optical semiconductor and optical semiconductor device

    JP2014150221A

  • Mold release polyester film and green sheet laminate

    JP2017061037A